ANALISIS KONTRIBUSI BUDIDAYA IKAN PATIN (Pangasius) TERHADAP PENDAPATAN TOTAL KELUARGA DI DESA SIDOGEDE KECAMATAN BELITANG KABUPATEN OKU TIMUR - Lutfi Al Wusqo, Sugeng Suprianto, Iman Sulaiman, Sudarti, (JASEP, 2024)
The aim of this research is to analyze the income contribution of catfish farming businesses. The research was conducted in Sidogede Village, Belitang District, East OKU Regency. One catfish pond in Sidogede Village, Belitang District, East OKU Regency measures 9 x 16 m², where there are 12 ponds, so the total area is 1800 m². The income received by the respondent was IDR 240,000,000.00 and the total income was IDR 216,017,91.00. So the respondent's income for six months was IDR 23,982,083.00 and income in one month was IDR 3,997,014.00. Catfish cultivation contributes in the medium category to total family income, namely 37.72%.